Pembuatan Film Selulosa dari Nata de Pina - Iskandar, Iskandar; Zaki, Muhammad; Mulyati, Sri; Fathanah, Umi; Sari, Indah; Juchairawati, Juchairawati (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2010)
Preparation of cellulose film from nata de pina, a product of pinapple fermentation, using acetobacter xylinum was done at room temperature for 15 days. The aim of the research is to investigate the effect of sugar concentration and pH on film quality. The fermentation run at sugar concentration of 0, 5, 7.5, 10 and 12.5% and at pH of 3, 5 and 7. Results show that the best nata de pina was obtained at sugar concentration of 10% and pH 5. At these conditions, maximum nata precipitates rendemen was 26,80%, with a moisture content of 80,55%, and the thickness of 3,30 cm. The product nata then can be used to produce cellulose film. The characteristic of the produced film were 8,20 Kgf/mm2 and 11,71% for maximum tensile strength and elongation, respectively.Keywords: acetobacter xylinum, film, nata de pina, selulosa